Characterization and management of Colletotrichum capsici causing anthracnose in chilli - V. PRAKASAM, P. AHILA DEVI* and (Indian Phytopathology, 2016)
The pathogen causing the anthracnose was identified as Colletotrichum capsici. RAPD profile was compared with the other patterns and Euclidean distance matrix was calculated for C. capsici from various ecosystems of Tamil Nadu. The isolate Cc1 was found to produce the toxic fraction C14C22O (2 tert-butyl-4- isopropyl-5-methyl). The toxic fraction C12H21NO2 (2,4,6 trimethyl phenyl glyoxylate) was produced by Cc8, where as the toxic fraction C12H14N03(4-dimethylaminomethyl-3-cyclohexane-1-carboxylate) was seen in Cc10. The residues of mancozeb were below detectable level (BDL) in the chilli samples 7 days after application of Carbendazim 12% + Mancozeb 63%@ 0.15% and 0.3%.